Evaluating school-based sexual health education programme in Nepal: An outcome from a randomised controlled trial. (2017) - Acharya, Dev; Thomas, Malcolm; Cann, Rosemary
Highlights: A trial is conducted to observe the teaching of sex education in schools. Health facilitator-led sex education programme is more effective. An informal teaching approach is useful in engaging students in the classroom. Training provides a sense of confidence and ownership to the tutors. Abstract: This study explored the effectiveness of teaching sex education programme to the secondary school children in Nepal.The study included four schools which were randomised to two groups; control and experimental schools. The teachers in the control schools delivered the sex education curriculum in a conventional way whereas the trained health facilitator in the experimental schools used a participatory teaching approach. The results were analysed by using z-score to identify the distribution patterns of pupils' responses. There was significant number of school children reporting the increment of sexual health knowledge in the experimental schools. This suggests that the health facilitator led sex education programme is more effective in improving the sexual health knowledge of the school children.